2023
DOI: 10.1177/00207640231174372
|View full text |Cite
|
Sign up to set email alerts
|

Mental health intervention research in Latin American correctional settings: A scoping review

Lukas Beigel,
Andrew Forrester,
Julio Torales
et al.

Abstract: Background: The Latin American prison population has grown faster than anywhere else globally over the past two decades, reaching a total of 1.7 million people at any given time. However, research on mental health prevention and treatment interventions in Latin American prisons remains scarce. Aims: This study aimed to systematically review and synthesize research on prison mental health interventions conducted in the region. Methods: We used a two-stage scoping review design guided by the JBI Manual for Evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Where studies have been undertaken they have indicated the needs for treatment of prisoners for mental health disorders have often not been identified and treatment needs have not been met (10,11). Few studies have examined what factors impact the pathway through the criminal justice system in terms of treatment received and whether needs were met, although some have suggested poorer outcomes for people from ethnic minority groups (12).…”
mentioning
confidence: 99%
“…Where studies have been undertaken they have indicated the needs for treatment of prisoners for mental health disorders have often not been identified and treatment needs have not been met (10,11). Few studies have examined what factors impact the pathway through the criminal justice system in terms of treatment received and whether needs were met, although some have suggested poorer outcomes for people from ethnic minority groups (12).…”
mentioning
confidence: 99%